2010
DOI: 10.1007/s10803-010-1161-1
|View full text |Cite
|
Sign up to set email alerts
|

No Proprioceptive Deficits in Autism Despite Movement-Related Sensory and Execution Impairments

Abstract: Autism spectrum disorder (ASD) often involves sensory and motor problems, yet the proprioceptive sense of limb position has not been directly assessed. We used three tasks to assess proprioception in adolescents with ASD who had motor and sensory perceptual abnormalities, and compared them to age- and IQ-matched controls. Results showed no group differences in proprioceptive accuracy or precision during active or passive tasks. Both groups showed (a) biases in elbow angle accuracy that varied with joint positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 38 publications
2
41
2
1
Order By: Relevance
“…The enhanced proprioceptive performance of individuals with ASD-like traits in the present study (and in the ASD group in our previous rubber-hand illusion study ;Paton et al, 2012) conflicts somewhat with a recent study examining limb proprioception in ASD outside of the context of sensory illusions (Fuentes, Mostofsky, & Bastian, 2011). In particular, no differences were found in this latter study in the accuracy and precision of proprioceptive estimates regarding arm position between individuals with ASD and healthy controls.…”
Section: Discussioncontrasting
confidence: 98%
“…The enhanced proprioceptive performance of individuals with ASD-like traits in the present study (and in the ASD group in our previous rubber-hand illusion study ;Paton et al, 2012) conflicts somewhat with a recent study examining limb proprioception in ASD outside of the context of sensory illusions (Fuentes, Mostofsky, & Bastian, 2011). In particular, no differences were found in this latter study in the accuracy and precision of proprioceptive estimates regarding arm position between individuals with ASD and healthy controls.…”
Section: Discussioncontrasting
confidence: 98%
“…Even though we cannot fully rule out this possibility, studies assessing vestibular function in ASD suggest intact vestibuloocular reflex function in studies assessing children (Goldberg, Landa, Lasker, Cooper, & Zee, 2000) and children and adults with ASD (Furman, Osorio, & Minshew, 2015). This evidence is in line with the intact nature of sensory information in ASD, including lowlevel visual information (Bertone et al, 2005;Pellicano et al, 2005;Pellicano & Gibson, 2008) and proprioceptive acuity (Fuentes et al, 2011).…”
Section: Postural Control In Autism Spectrum Disorder 16mentioning
confidence: 53%
“…For example, Pellicano and Gibson (2008) assessed integrity of dorsal stream visual processing in ASD and showed that children with ASD exhibited intact lower-level but impaired higher-level dorsal stream functioning. In a similar vein, proprioception was assessed in adolescents with ASD and Typically Developing (TD) controls using proprioceptive matching tasks (Fuentes, Mostofsky, & Bastian, 2011). In this study, although ASD participants were impaired in general sensory and motor performance, their proprioceptive abilities were not different from typically developing adolescents'.…”
mentioning
confidence: 93%
“…B 282: 20141557 illusion in movement. While there is evidence that proprioceptive estimates in non-illusory conditions are no more accurate or precise in ASD than in controls [46], this study differs in incorporating an uncertain context in which conflict between cues for arm position derived from the illusion and proprioceptive input during illusion induction may induce an expectation for low precision in the sensory input. That is, sensorimotor input can normally be interpreted unequivocally under long-held, very stable expectations about body-image, body-schema and bodily self-awareness, but the RHI challenges these expectations and throws doubt on the sensory input.…”
Section: Discussionmentioning
confidence: 90%